AB0856 Ultra Sonographic Confirmation of Enthesitis in Patients with Fibromyalgia. (10th June 2014) - Michael, C.; Alyas, F.; Georgiou, A.; Roussou, E.
Abstract : Background: Aiming to evaluate whether the clinical overlap identified and presented before [1] between enthesitis sites (ES) and Fibromyalgia (FM) tender points (TeP) in patients with Inflammatory back pain corresponds to radiologically confirmed enthesitis, we assessed by ultrasonography (u/s) the FMTeP in patients with confirmed FM fulfilling both 1999 and 2011 criteria. Methods: A mannequin with the clinically identified FMTeP has been given to a musculoskeletal radiologist requesting ultra sonographic study of the indicated FMTeP aiming to exclude or confirm enthesopathic disease. No other joints or entheses have been evaluated. The machine used was a routinely used ultrasonographic machined for routine patients. Results: A total of 338 tender points have been evaluated by u/s from a total of 29 patients with FM (m:F = 2:27; Caucasian:Asian = 22:7). Patients had a mean age of 45.1 years (±11.1) and age of disease onset of 35.2 (±11.8). From the 338 tender points examined 84 enthesitis sites have been identified (24.8%). A total of 27 of 29 patients (93%) had a positive u/s scan by having at least 1 identified ES from the ones pointed out as clinically tender points on the mannequin. Patients had between 1 and 8 ES. One patient had 8 ES identified, 2 patients had 7 ES, 3 patients had 1, 3, 5 and 6 ES identified respectively (total 45 sites) and 6 patients had 2 ES. Right and Left grater trochanter had the most ES detected (14 for each one of them, 12 of which were bilateral on the same patients), followed by left (L) common extensor in the elbow (n=13 patients) right (R) common extensor in the elbow (n=10 patients) L) medial collateral Knee (n=9), R) medial collateral Knee (n=8), L) costochondral (n=7), R) costochondral and posterior superior iliac crest (n=6), L) posterior superior iliac crest (n=5). No ES identified in the cervical fascia bilaterally. Conclusions: Patients with FM have confirmed sonographic enthesitis most frequently being that of trochanteric bursitis followed by common extensor tendinitis from the elbows. References: E. Roussou & C. Ciurtin.-Clin. Exp. Rheum.2012;30(74): 24-30 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2585